Initial Effectiveness of Instagram Reels-Based Motion Graphics for Introducing Ludruk to Generation Z - Nugrahardi Ramadhani; Didit Prasetyo; Kartika Kusuma Wardani; Tedi Mursalat Farqo; Adisa Salma Raihana (JPI: Jurnal Pustaka Indonesia, 2026)
Ludruk, a traditional theatrical art form from East Java, is increasingly marginalized among younger audiences, particularly Generation Z, whose media consumption is shaped by short, visual, and platform-based digital content. This study aimed to develop Instagram Reels-based motion graphics as digital learning media for introducing ludruk to Generation Z and to examine their initial effectiveness. The study employed the Multimedia Development Life Cycle (MDLC) framework and involved qualitative and quantitative data collection through literature review, questionnaires, observation, interviews, and user testing. The needs-analysis stage involved 40 respondents from the target audience group, while the user-testing stage involved 30 participants. The final product consisted of four short motion graphic videos, each lasting less than three minutes, designed with dynamic visuals, light narration, and culturally adapted humor to align with the communication preferences of Generation Z. User-testing results showed a substantial increase in participants’ understanding, with a mean N-gain score of 0.8, which falls into the high category. These findings indicate that Instagram Reels-based motion graphics have promising initial effectiveness as digital learning media for introducing ludruk and may serve as an accessible entry point for strengthening cultural literacy among younger audiences.